The Development Of Natural Potential Of Ponggok Village As Recreational Sports And Water Sports Tourism For Regional People In Klaten Regency - Muhammad Rusyanto Fitriantono; Agus Kristiyanto; Siswandari Siswandari (Kazimierz Wielki University, 2019)
The main objective of this research is to explain the management of the natural potential of Ponggok Village Klaten, describe the development of recreational sports and water sports tourism in Ponggok Village Klaten, and explain the role of Ponggok Village to support tourism development in Klaten Regency. This research is conducted in Ponggok Village, Klaten Regency, Central Java Province, using qualitative research and phenomenology approach. The data collection techniques used in this study are observation, deep interviews, and documentation. The results of the research are summarized as follows: 1) The natural potential of Ponggok Village Klaten are in the agricultural sector and water sector, that is supported by springs or usually known as umbuls. In the agricultural sector, people mostly plant rice. Meanwhile, the springs are used for fishery and tourism. In the fishery sector, there are several freshwater fish farming ponds. The tourism sector in Ponggok Village utilizes several umbuls including Umbul Ponggok, Umbul Ponggok Ciblon, Umbul Kapilaler, Umbul Sigedang, and Umbul Besuki. Most of the umbuls in Ponggok Village are used for recreational sports, such as swimming. Umbul Ponggok is also used for swimming, diving, and snorkeling. 2) The development of recreational sports and water sports tourism in Umbul Ponggok that was only used for swimming by visitors around Ponggok Village, now is even more developing. There are some more facilities such as rental mask snorkels and buoys for snorkeling, scuba set for diving, and Ponggok Walker for walking under water. There is also Ponggok Warior as mini outbound on water for children. Besides, there is a slide for stimulating adrenaline which is directly connected to the umbul. In Umbul Ponggok Ciblon, there are three swimming pools and parks that can be used for outbound activities. People also often use ponds in Umbul Ponggok Ciblon to swim, usually in the afternoon. In Umbul Kapilaler that is surrounded by big trees, visitors usually come to swim and play with water. 3) Ponggok Village is already quite popular among the President, the Ministers, the House of Representative members etc. The delegation of 20 countries of The Asian Productivity Organization (APO) also visit Ponggok Village. The Minister of Rural Development Malaysia also come to Ponggok Village and made 10 Village Heads of Malaysia wanted to take a closer look at Ponggok Village. Ponggok village certainly brings the name of Klaten Regency well known domestically and internationally. Ponggok has the potential that might be here only. People can enjoy the beauty and take pictures under fresh water. The water is very clear; it is hard to find elsewhere. Ponggok Village has its own uniqueness as a tourist attraction.